2021
DOI: 10.1007/s10067-021-05830-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with COVID-19 and its outcome in patients with rheumatoid arthritis

Abstract: Objective We assessed the factors associated with COVID-19, clinical manifestations, and a 30-day-prognosis of COVID-19 in a cohort of rheumatoid arthritis (RA) patients compared with the index population. Methods In a cross-sectional study, RA patients were followed in rheumatology clinics of Tabriz University of Medical Sciences, and a group of patients diagnosed with COVID-19 from index population were recruited. Outcomes of COVID-19 were assessed by the hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 12 publications
7
20
0
1
Order By: Relevance
“…However, GC use was significantly associated with both of these poor outcomes. Additionally, on primary analysis, the risks for all complications and adverse outcomes were significantly higher in patients with RA [45]. But after propensity matching for age and comorbidities, the risks for adverse outcomes with RA did not differ as compared to non-RA patients except for sepsis and venous thromboembolism [46].…”
Section: Rheumatoid Arthritismentioning
confidence: 92%
See 3 more Smart Citations
“…However, GC use was significantly associated with both of these poor outcomes. Additionally, on primary analysis, the risks for all complications and adverse outcomes were significantly higher in patients with RA [45]. But after propensity matching for age and comorbidities, the risks for adverse outcomes with RA did not differ as compared to non-RA patients except for sepsis and venous thromboembolism [46].…”
Section: Rheumatoid Arthritismentioning
confidence: 92%
“…Similarly, a cross-sectional study in Iran analyzed 128 patients with RA and COVID-19 and found an increased risk of infection and hospitalization with DM on univariate and multivariate analysis [42]. Another comparative study from the TriNetX in the USA did not find an association between DM and hospitalization or death [45]. However, GC use was significantly associated with both of these poor outcomes.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 2 more Smart Citations
“…One study has identified a higher risk of venous thromboembolism in RA patients that have contracted the infection, with glucocorticoids only increasing the risk of adverse effects [ 58 ], whereas systemic therapies did not influence it [ 34 ], nor did other classes of disease-modifying antirheumatic drugs [ 64 ]. On the other hand, one study has suggested that respiratory viral infections might be in fact a risk factor for the development of RA [ 65 ], but treatments with prednisolone and TNFα inhibitors (TNFis) increase the risk of COVID-19 [ 36 ], and the risk of hospital admissions [ 29 ] in RA patients with comorbidities such as diabetes. Two studies have found contradicting results; one found no association between RA and COVID-19 in a cohort study in South Korea [ 31 ], whereas the other stated that RA patients are more prone to the infection due to the iatrogenic effects of the RA medications [ 30 ].…”
Section: Orthopedic Conditions and Covid-19mentioning
confidence: 99%